Delivery of antigen to porcine dendritic cells by fusing antigen with porcine dendritic cells targeting peptide - Xia, Tian; Wang, Ning; Tang, Yuqing; Gao, Yueyi; Gao, Chong; Hao, Jianhui; Jiang, Yanping; Wang, Xiaona; Shan, Zhifu; Li, Jiaxuan; Zhou, Han; Cui, Wen; et al. (Frontiers in Immunology, 2022)
Dendritic cells (DCs) are professional antigen-presenting cells that can recognize, capture, and process antigens. Fusing molecules targeting DCs with antigens can effectively improve the efficiency with which antigens are recognized and captured by DCs. This targeting strategy can be used for vaccine development to effectively improve the efficiency of antigen recognition and capture by DCs. The targeting sequence of porcine cytotoxic T-lymphocyte associated protein 4 (CTLA4), which binds porcine DCs, was identified in this study. Recombinant Lactobacillus reuteri (L. reuteri) expressing CTLA4-6aa (LYPPPY) and CTLA4-87aa fused to the porcine epidemic diarrhea virus (PEDV) protective antigen core neutralizing epitope (COE) were used to evaluate the ability of the two targeting motifs to bind the B7 molecule on DCs. Our results demonstrate that CTLA4-6aa could bind porcine DCs, and recombinant Lactobacillus expressing the CTLA4-6aa captured by porcine DCs was more efficient than those expressing CTLA4-87aa. In addition, the expression of DC markers, toll-like receptors, and cytokines was significantly higher in the 6aa-COE/L. reuteri-stimulated porcine DCs compared to DCs treated with 87aa-COE/L. reuteri (p<0.01) and recombinant Lactobacillus expressing CTLA4-6aa enhanced the ability of porcine DCs to activate T-cell proliferation. Our analysis of the protein structure revealed that CTLA4-87aa contains intramolecular hydrogen bonds, which may have weakened the intermolecular force between the residues on porcine CTLA4 and that on B7. In conclusion, recombinant Lactobacillus expressing CTLA4-6aa were more efficiently captured by porcine DCs and had a stronger ability to promote DC maturation and enhance T-cell proliferation. The LYPPPY motif is the optimal sequence for binding to porcine DCs. Piglets immunized with recombinant Lactobacillus showed that recombinant Lactobacillus expressing CTLA4-6aa induced significant levels of anti-PEDV-specific IgG and IgA antibody responses. Our study may promote research on DC-targeting strategies to enhance the effectiveness of porcine vaccines.